Assessment of Thatch Grass Harvesting Model in Protected Areas and Its Role as an Additional Livelihood Option for Woman in North West Matabeleland, Zimbabwe - Mukululi, Ndlovu; Aleck, Makumire; Agness, Simakani; Thulani, Jele; Tinaapi, Madiri Hilary (Journal of Sustainable Natural Resources, 2023)
Thatch grass is a readily available ecosystem products that plays a direct economic and utilitarian benefit to woman in households surrounding the protected areas of Zimbabwe. The study describes the institutional arrangement in place for the exploitation and lesson highlights of thatch grass in the protected areas of Matetsi Safari Area and Kazuma pan national park in North West Matebeleland region. The arrangement for thatch grass harvesting is that only the women (young and elderly) are allowed to apply for thatch grass harvesting in protected areas for defined period of time usually two weeks. We used park registers of thatch grass harvesters to determine the number of women involved, thatch grass bundles harvested and villages involved. At total of 15 744 bundles of thatch grass were harvested in the year 2022. The total bundles that the woman took home were 10 962 while 4 784 were retained by the park or concession holders. On average, an individual woman collected 27 to 125 bundles. Each individual woman direct income from thatch grass harvesting ranged from US$ 40 to US$187 per harvesting season. The key lesson in the thatch grass arrangement is that woman can successfully be mainstreamed directly to benefit from protected areas without experiencing negative effects associated with resource access in protected such as wildlife poaching which might occur when men are involved. Further, coordinated thatch grass harvesting has less conflict with the trophy hunting experience and activities in the hunting areas. While some challenges have been experienced in the national park component, the challenges are partly due to the perceived regulations, purpose of national parks and the somewhat negative attitude of stakeholders operating in the park to use of natural resource by local communities. In order for the thatch grass harvesting to remain sustainable and compatible with activities in the protected area there ought to be planning, coordination, monitoring of harvesting activities and ongoing ecological monitoring of potential ecosystem impacts.